Optimization of Electro-Fenton Process in Reducing COD and TSS Levels in Batik Wastewater - Ramadeandra, Shafa Azzahra; Rosariawari, Firra (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Batik industries, ranging from household-scale to large-scale, generate wastewater containing high levels of organic compounds, dyes, and other pollutants such as COD (Chemical Oxygen Demand) and TSS (Total Suspended Solids), which are difficult to degrade. Wastewater treatment is necessary to reduce pollutant content to meet environmental quality standards. Therefore, this study investigates the effectiveness of the Advanced Oxidation Process (AOP) using the electro-Fenton method. The objective of this research is to analyse the effectiveness of and optimise the ElectroFenton process for reducing COD and TSS in batik wastewater. The study aims to determine the optimal combination of current intensity, contact time, and molar ratio of H2O2:FeSO4 that yields the highest removal efficiency. Based on the survey, the electro-Fenton treatment achieved a COD removal efficiency of 77.14% under conditions of 5 amperes current, 55 minutes contact time, and ratio of 10:0.3. At a current of 3 amperes, a contact time of 55 minutes, and a ratio of 10:0.3, the TSS removal efficiency was 98.3%. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 12: Responsible Consumption and ProductionSDG 14: Life Below WaterSDG 15: Life on Land